The Psychometric Properties of the Norwegian Parent Version of Developmental Behavior Checklist (DBC-P) - Halvorsen, Marianne; Helverschou, Sissel Berge (PsykTestBarn, 2020)
Description: The DBC-P was developed by Stewart Einfeld and Bruce Tonge in Australia in 1992. A Norwegian version is currently only available for research purposes through Western Psychological Services. The checklist has recently been adapted and standardized for use in USA, and there is contact between international copyright holder and a Norwegian publisher in order to publish a Norwegian version for clinical use. The DBC-P is a 96-item instrument designed to assess the presence and severity of behavioural and emotional problems in children and young people with developmental and intellectual disabilities. It is completed by a parent or carer. It can be used in clinical practice in assessments and for monitoring the effect of interventions, and in research studies. Completing the checklist takes approximately 15 – 20 minutes. Literature search: A systematic review of studies on the psychometric properties of the Scandinavian versions of the DBC parent version identified 322 articles. Two Norwegian publications reporting data from the same sample were finally included. They included individuals with Smith-Magenis syndrome from the ages of 5-50 with varying degrees of intellectual disability. Mean raw scores for the DBC and documentation on construct validity were given. Psychometrics: Mean values for DBC scales in the sample of people with Smith-Magenis syndrome were significantly higher than the original norms. Discriminant validity was demonstrated through associations between DBC and Vineland-II. Convergent validity was demonstrated by the association between DBC Social Relating and autism symptoms measured by the Social Responsiveness Scale Conclusion: The DBC parent version's psychometric properties in Norway and Scandinavia have not been sufficiently investigated.